2021
DOI: 10.1093/ageing/afab082
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission as a deprescribing triage point for patients discharged to Residential Aged Care Facilities

Abstract: Background Deprescribing may benefit older frail patients experiencing polypharmacy. We investigated the scope for deprescribing in acutely hospitalised patients and the long-term implications of continuation of medications that could potentially be deprescribed. Methods Acutely hospitalised patients (n = 170) discharged to Residential Aged Care Facilities, ≥75 years and receiving ≥5 regular medications were assessed during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several systematic reviews of deprescribing have not demonstrated a benefit associated with reducing medication burden. 3,4 Our study found no deterioration in HRQOL for the group who had medications deprescribed, but a faster readmission. Furthermore, we found worse mortality in those patients ceasing antihypertensives and statins.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Several systematic reviews of deprescribing have not demonstrated a benefit associated with reducing medication burden. 3,4 Our study found no deterioration in HRQOL for the group who had medications deprescribed, but a faster readmission. Furthermore, we found worse mortality in those patients ceasing antihypertensives and statins.…”
Section: Discussionmentioning
confidence: 50%
“…2 An unplanned hospitalisation becomes a conduit of new prescriptions to treat symptoms and prevent major clinical events. 3 Therefore, it is no surprise that the hospital is a common source of potentially inappropriate medications (PIM) and can exacerbate, rather than reduce exposure to polypharmacy. 2 Deprescribing, whether inpatient or outpatient, has been promoted as a solution to the vexing problem of polypharmacy and a way to improve the negative outcomes attending polypharmacy, 4 but systematic reviews of this approach have been unable to support a clear and consistent benefit.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Potential limitations also need to be acknowledged. In particular, medication changes during hospitalization, including targeted deprescribing strategies (Tay et al, 2014;Russell et al, 2019;Kaminaga et al, 2021;Roberts et al, 2021;Russell et al, 2021;Scott et al, 2021), inevitably lead to deviations from the medication list on admission. This, however, could be rectified by additional linkage to discharge and/or readmission data.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive polypharmacy (e.g., 10 or more medications) is especially prevalent in nursing homes and was also associated with excessive death [adjusted OR 1.96 (1.42–2.71)] [9 ▪ ,10]. Excessive polypharmacy was also common at the hospital admission in elderly patients aged at least 75 from nursing homes settings (49.4%), and therefore deprescribing strategies are recommended [20 ▪ ]. Dementia incidence has been increased significantly with the increase in the number of prescribed drugs and polypharmacy (cohort study in South Korea, n = 1025 340), which represents a serious risk for dementia (5–<10 drugs: 2.64, 95% CI: 2.32–3.05; ≥10 drugs: 3.35, 95% CI: 2.38–4.71; <1 drug used as reference) [21].…”
Section: Polypharmacy In Elderly Patients With Schizophreniamentioning
confidence: 99%